Winning Research Funding, 1st edition - Abby Day, Peters (Routledge, 2020)
This book gives advice on writing and successful publication following completion of the research project and features real-life case studies and interviews throughout. It explains how to build and maintain a relationship with the research partner, thereby assisting future research.